Estilos de personalidad y tipos de afrontamiento al estrés en Policías. Tungurahua, 2021 - Morales Castillo, Jeniffer Estefanía (2022)
This investigation was carried out in Police Subzone No. 18 in Ambato city. The main objective was to analyze the personality styles and types of coping in police officers of Subzone N ° 18 in the period May 2021 - October 2021. It was carried out with a sample of 153 participants. The research was of field and bibliographic type, with a cross-sectional design and a descriptive level. The instruments used were the Millon Personality Styles Inventory (MIPS) to identify personality styles and the Stress Coping Questionnaire (CAE) to determine the types of coping. The results obtained were that the most used personality styles correspond to individualism with 62.74%, sensation with 54.24%, conformity with 53.59%, and systematization with 51.63% and, regarding the types of coping with stress, mean scores were obtained, where it is mostly used: focusing on the solution of the problem with 15.71 and positive reassessment with 13.59. According to the information obtained, an intervention proposal was prepared through a psychoeducational triptych.